COASTLINE CHANGES AT BUNGUS BAY PADANG CITY, WEST SUMATERA PROVINCE BASED ON SATELLITE IMAGERY ANALYSES - Yulius Yulius; M. Ramdhan (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
The Bungus Bay with ​​21,050 meters of coastline length and 1,383.86 ha of surface area confines with a rounded shape surface. This study aimed to determine coastline changes in the Bungus Bay based on overlay analyses of satellite imagery of 2000, 2006, 2010, and 2011. The method used in this research was visual interpretation using four key interpretation such as hue image, texture association, and shape. The results showed that in general there were abrasion processes in the Bungus Bay. The abrasion processes were more dominant in the Buo Bay, Kaluang Bay, and Kabuang Bay. The largest coastline changes occurred in the northern Bungus Bay for 26 m/yr, while in the Kaluang Bay and Kabuang Bay exhibited a moderate change of 9 m/yr. In general, the rate of coastline change in the Bungus Bay was 5.9 m/yr.Keywords: abration, accretion, coastline changes, Bungus Bay